2020
DOI: 10.3389/fmed.2020.546445
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Inhibits NLRP3 Inflammasome Activation in Nonalcoholic Steatohepatitis via AMPK-JNK/ErK1/2-NFκB/ROS Signaling Pathways

Abstract: Adiponectin, an adipose-derived adipokine, possesses a hepatoprotective role in various liver disorders. It has been reported that hypoadiponectinemia can affect with the progression of non-alcoholic fatty liver diseases (NAFLD). Inflammasome activation has been recognized to play a major role during the progression of NAFLD. This research aimed to explore the effect of adiponectin on palmitate (PA)-mediated NLRP3 inflammasome activation and its potential molecular mechanisms. Male adiponectin-knockout (adipon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
(54 reference statements)
0
26
1
Order By: Relevance
“… [15] DAMPs and PAMPs activate PRRs like TLRs and nucleotide-binding oligomerization domain-containing protein 2 (NOD2) with subsequent stimulation of NFκB pathway. [16] This priming contributes to macrophage activation and increase the expression of IL1β gene with post-translation modification of NLRP3 inflammasome through modulation of the activation of cell membrane ion channels, lysosome disruption and mitochondrial dysfunction. [17] In addition, activation of NLRP3 inflammasome induces T cells pyroptosis via gasdermin D (GSDMD) dependent-activation of caspase 1, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“… [15] DAMPs and PAMPs activate PRRs like TLRs and nucleotide-binding oligomerization domain-containing protein 2 (NOD2) with subsequent stimulation of NFκB pathway. [16] This priming contributes to macrophage activation and increase the expression of IL1β gene with post-translation modification of NLRP3 inflammasome through modulation of the activation of cell membrane ion channels, lysosome disruption and mitochondrial dysfunction. [17] In addition, activation of NLRP3 inflammasome induces T cells pyroptosis via gasdermin D (GSDMD) dependent-activation of caspase 1, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psoriasis complicated by NAFLD have been shown to have lower adiponectin levels than patients with psoriasis alone [ 126 , 127 ]. An in vivo study has shown that adiponectin deficiency not only increase the expression of NF-κB, but also promote the accumulation of lipid droplets and increase the production of reactive oxygen species (ROS), thereby aggravating liver damage and steatosis in an HFD-induced NAFLD mouse model [ 128 ]. In patients with psoriasis, it is reasonable to speculate that the reduction in adiponectin may play a role in promoting the development of NAFLD.…”
Section: Adiponectin and Psoriasis Comorbiditiesmentioning
confidence: 99%
“…As mentioned, GLP-1RAs can treat NAFLD through multiple mechanisms. Adiponectin was reported to reduce NAFLD inflammation through the AMPK-JNK/ErK1/2-NFκB/ROS signaling pathway, also exhibiting insulin sensitization and liver protection ( 196 ). A recent report covered that tirzepatide increased adiponectin levels and significantly decreased Nash related biomarkers, which was beneficial to improve NAFLD ( 197 ).…”
Section: Effects On Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%